Visualization of grout diffusion in coarse-grained materials using transparent soil: Effects of Fine particle content - Shihao Zhang; Jianxin Wang; Zhuo Li; Yusheng Li (PLoS ONE, 2026)
Fine-particle loss in earth-rock dams can induce abnormal grout diffusion during rehabilitation. To address this issue, we investigated the influence of fine particle content on grouting efficiency in coarse-grained materials. Using transparent soil technology, coarse-grained materials were simulated with fused quartz sand and a refractive-index-matched pore fluid (n = 1.4585). Dyed epoxy resin was used as a cement grout analog. Constant-pressure grouting tests (40 kPa) were performed on three test conditions representing no fine-particle loss, partial fine-pareicle loss, and complete fine-particle loss. The grout diffusion process was visualized and quantified using Particle Image Velocimetry (PIV). The results reveal that fine particle content critically controls grout diffusion patterns and rates. (1) Excessive fines cause pore clogging, resulting in grout upwelling, surface seepage, and limited diffusion, forming locally consolidated masses with blocky bonding. (2) An appropriate fine particle content enables uniform spherical diffusion, creating an optimized structure characterized by point bonding of large particles and small-pore filling. (3) The absence of fines leads to gravity-dominated rapid settlement with weak horizontal diffusion, leaving only surface-coated particles. This study elucidates the coupled mechanisms of fine-particle migration, clogging, and grout diffusion, providing an experimental basis for optimizing permeation grouting in coarse aggregates.